2022
DOI: 10.1002/pbc.29857
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hiring a full‐time fertility navigator on fertility‐related care and fertility preservation at a pediatric institution

Abstract: Fertility navigators (FNs) are important in communicating infertility risk and fertility preservation (FP) options to patients receiving gonadotoxic therapies. This retrospective study examined electronic medical records of patients with fertility consults at a large pediatric institution (2017-2019), before and after hiring a full-time FN. Of 738 patient encounters, 173 consults were performed pre-navigator and 565 postnavigator. Fertility consults for long-term follow-up cancer survivors increased most subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Additionally, the providers were aware that this project was taking place and kept the FPC updated on newly diagnosed patients, which contributed to the high rate of assessed patients. Similar studies have demonstrated the impact of hiring an FPC on education rates (Dorfman et al, 2021; Wright et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, the providers were aware that this project was taking place and kept the FPC updated on newly diagnosed patients, which contributed to the high rate of assessed patients. Similar studies have demonstrated the impact of hiring an FPC on education rates (Dorfman et al, 2021; Wright et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…The addition of a dedicated fertility team with APN navigator has been shown to increase referrals for fertility counseling both before therapy and in survivorship (28). Inclusion of a fertility navigator in the multidisciplinary approach to children and adolescents diagnosed with has demonstrated an increase in both patient and provider satisfaction as well as improved outcomes by connecting multiple teams with different priorities across the healthcare system (29).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many efforts to make fertility preservation a routinary discussion after cancer diagnosis, there are still many barriers that limit the access to those treatments [30]. The implementation of formal oncofertility programs and strategies to provide patient information have successfully improved the rates of fertility preservation consultation and semen cryopreservation in some institutions [31 ▪ ,32 ▪ ,33,34]. After launching a fertility preservation program, Sheth et al [33] organized in-service educational seminars to teach and train oncology physicians and nurses about fertility preservation options and procedures.…”
Section: Addresing Current Gaps In the Systemmentioning
confidence: 99%
“…The full implementation of these program resulted in a 2.7-fold increase in semen cryopreservation. More recently, a large pediatric institution hired a full-time navigator on fertility related care and fertility preservation options for patients receiving gonadotoxic therapies; This resulted in a marked increase in fertility preservation consults [31 ▪ ].…”
Section: Addresing Current Gaps In the Systemmentioning
confidence: 99%